Organizational Improvisation and Organizational Memory - Moorman, Christine; Miner, Anne S. (Academy of Management Review, 1998)
We define organizational improvisation as the degree to which the composition and execution of an action converge in time, and we examine the theoretical potential of this definition. We then propose that both organizational procedural memory (skill knowledge) and declarative memory (fact knowledge) moderate improvisation's impact on organizational outcomes in distinct ways. We also suggest that improvisation influences organizational memory by (1) generating experiments and (2) permitting the development of higher-level competency in improvisation. Contemporary technological changes related to the nature of organizational memory intensify the salience of these issues.